Expression of functional alternative telomerase RNA component gene in mouse brain and in motor neurons cells protects from oxidative stress - Eitan, Erez (Oncotarget, 2016)
Telomerase, a ribonucleoprotein, is highly expressed and active in many tumor cells and types, therefore it is considered to be a target for anti-cancer agents. On the other hand, recent studies demonstrated that activation of telomerase is a potential therapeutic target for age related diseases. Telomerase mainly consists of a catalytic protein subunit with a reverse transcription activity (TERT) and an RNA component (TERC), a long non-coding RNA, which serves as a template for the re-elongation of telomeres by TERT. We previously showed that TERT is highly expressed in distinct neuronal cells of the mouse brain and its expression declined with age. To understand the role of telomerase in non-mitotic, fully differentiated cells such neurons we here examined the expression of the other component, TERC, in mouse brain. Surprisingly, by first using bioinformatics analysis, we identified an alternative TERC gene (alTERC) in the mouse genome. Using further experimental approaches we described the presence of a functional alTERC in the mouse brain and spleen, in cultures of motor neurons- like cells and neuroblastoma tumor cells. The alTERC is similar (87%) to mouse TERC (mTERC) with a deletion of 18 bp in the TERC conserved region 4 (CR4). This alTERC gene is expressed and its product interacts with the endogenous mTERT protein and with an exogenous human TERT protein (hTERT) to form an active enzyme. Overexpression of the alTERC and the mTERC genes, in mouse motor neurons like cells, increased the activity of TERT without affecting its protein level. Under oxidative stress conditions, alTERC significantly increased the survival of motor neurons cells without altering the level of TERT protein or its activity. The results suggest that the expression of the alTERC gene in the mouse brain provides an additional way for regulating telomerase activity under normal and stress conditions and confers protection to neuronal cells from oxidative stress.